Taṭwīr Lu’bah al-Mugāmarah al-Lugah al-Arabiyyah SI UJE al-Qāimah ‘ala Android li Talāmīż al-Ṣaf al-Ṡāmin fi al-Madrasah al-Ṡānawiyyah. - Hafidah Hafidah; Witri Lestari; Muhammad Nur Kholis; Moh Nurul Huda (Arabic Education Program IAIN Pekalongan, 2021)
The implementation of Arabic learning activities at State Islamic Junior High School of 2 Jakarta, especially during the Covid-19 period, was carried out online or distance learning. But in addition, the problem faced is that the teacher uses the lecture method so that learning becomes boring because students are only listeners. As a result, it affects students' interest in teaching Arabic because it is considered monotonous. The purpose of this research is to developing the SI UJE Arabic Adventure Game based on Android and to find out its validity, practicality and effectiveness. This type of research is research and development with the ADDIE research model. The results of the validation questionnaire by media experts are 88% and material experts are 97% and both are in the very good category. Then the teacher's response was 92% and the students of grades 84 and 85 were 98% and 95% and all of them were in the very practical category. The test results for students in grade 84 are 100% and 88.8%, while for students in grade 85 are 100% and 83% are categorized as very effective.